Process evaluation of a whole-of-community systems approach to address childhood obesity in western Victoria, Australia - Ebony Jenkins; Janette Lowe; Steven Allender; Kristy A. Bolton (BMC, 2020)
Abstract Background SEA Change Portland is a systems-based approach implemented in Portland, Victoria that utilises local community resources to sustainably prevent and reduce the prevalence of childhood obesity. Action is implemented by community-led task teams with differing priority areas, and supported by a steering committee representative of four collaborating organisations. This study examines the SEA Change Portland process to identify significant events, enablers and barriers of its development and implementation to date as reported by key stakeholders involved in implementation during the first 12 months. Methods Semi-structured interviews were conducted with eight steering group members and three community task team members. Data was collected utilising open ended interview questions to gather in-depth information regarding program implementation, and the individual attitudes, beliefs and experiences of key stakeholders. Results Data were analysed under three key themes: collective impact, systems thinking and asset based community development (ABCD). Participants gave perceptions of significant events; factors positively and negatively affecting the process; reasons for becoming involved in the process; perceived efficacy of task teams, principles of diversity and areas of concern. Themes emerged from participant responses allowing were categorisation of their responses into four key process stages: initial lead up; process development; establishing community ownership of the obesity system; and community action. Conclusion Collective impact was a crucial element in applying the systems thinking. Strong and equitable relationships between steering organisations and topic experts provided the initiative with a sustainable foundation, and ABCD promotes community ownership and future sustainability. Understanding the process of implementing a new whole-of-community systems approach to childhood obesity prevention such as SEA Change Portland has provided vital knowledge for other communities regarding enablers and barriers of this promising approach.